Penguatan Ekonomi Pesantren Berbasis Digital: Aspek Manajemen Bisnis, Keuangan dan Permodalan - Usnan, Usnan; Rais Sani Muharrami; Asep Maulana Rohimat; Ghegana Ariel Sheda; Ersiana Riandani; Muhamad Umam Maulana (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Islamic boarding schools (pesantren) hold significant potential to become centers for economic empowerment based on Islamic values. This article describes the community engagement activities conducted by the FEBI UIN Raden Mas Said Surakarta team at Pondok Pesantren Muhammad Al-Fatih Kartasura. The program aims to strengthen the pesantren's economy through a digital-based approach, focusing on business management, financial management, and access to capital. The community engagement method employed is Participatory Action Research (PAR), involving intensive collaboration between the engagement team, pesantren leaders, and the student community. The results indicate that the pesantren faces challenges in terms of limited production resources, suboptimal marketing strategies, and unstructured financial management. This program provides solutions through entrepreneurial skills training, strengthening digital-based marketing, and technical assistance in basic financial management and access to capital